2006
DOI: 10.1196/annals.1378.062
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Oxidative Stress Status and Concentration of TGF‐β1 in the Blood and Saliva of Osteoporotic Subjects

Abstract: Preliminary reports indicate the influence of oxidative stress and interleukins, particularly TGF-beta1, in maintenance of bone mass. This study was designed to determine any possible variations of cellular lipid peroxidation, the total antioxidant power, and concentration of TGF-beta1 in blood and saliva of osteoporotic subjects in comparison to healthy people. Blood and saliva samples of 22 osteoporotic women and 22 age-matched healthy women were collected. Samples were analyzed for thiobarbituric acid-react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 39 publications
3
26
0
1
Order By: Relevance
“…Indeed, oxidative stress alters bone remodeling process causing an unbalance between osteoclast and osteoblast activity, this can lead to metabolic bone diseases and contribute to the pathogenesis of skeletal system disorders including osteoporosis characterized by low bone mineral density and decrease in bone mass, which makes the bone weak and more prone to fracture (18,(33)(34)(35)(36). Recent evidences in a limited number of clinical studies have shown that ROS and/or antioxidant systems can be involved in the pathogenesis of bone loss (36)(37)(38)(39). In fact, oxidative stress activates the differentiation of preosteoclasts in osteoclasts and strengthens the bone resorption (18,40) (Figure 1).…”
Section: Oxidative Stress In Bone Remodelingmentioning
confidence: 99%
“…Indeed, oxidative stress alters bone remodeling process causing an unbalance between osteoclast and osteoblast activity, this can lead to metabolic bone diseases and contribute to the pathogenesis of skeletal system disorders including osteoporosis characterized by low bone mineral density and decrease in bone mass, which makes the bone weak and more prone to fracture (18,(33)(34)(35)(36). Recent evidences in a limited number of clinical studies have shown that ROS and/or antioxidant systems can be involved in the pathogenesis of bone loss (36)(37)(38)(39). In fact, oxidative stress activates the differentiation of preosteoclasts in osteoclasts and strengthens the bone resorption (18,40) (Figure 1).…”
Section: Oxidative Stress In Bone Remodelingmentioning
confidence: 99%
“…Given this fact, every factor affecting this pathway will influence bone-remodeling cycle. Regarding the pathogenesis of osteoporosis, various investigations have demonstrated the association between inflammation, hormones, growth factors, paracrine and autocrine extractions, homocystein, oxidative stress, and bone fragility (Abdollahi et al 2005;Yousefzadeh et al 2006;Salari et al 2008a, b). In this regard, interleukin-1 (IL-1β) and tumor necrosis factor-α (TNF-α) provoke bone resorption.…”
mentioning
confidence: 99%
“…Also, lipidic peroxidation, quantified by thiobarbituric acidreactive substances (TBARS), was also higher in both blood and saliva in a group of 22 postmenopausal osteoporotic women (also showing lower antioxidant-capacity) in relation to 22 control ones (Yousefzadeh et al, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 97%